2016
DOI: 10.1071/ah15156
|View full text |Cite
|
Sign up to set email alerts
|

Survey of research activity among multidisciplinary health professionals

Abstract: Objective The aim of the present study was to describe the research activities being undertaken by health service employees within one Australian health service and explore their experiences with undertaking research. Methods The present mixed-methods study was conducted across one health service in Queensland, Australia, and included a cross-sectional online survey and interviews with healthcare service employees. The anonymous survey was a self-administered online questionnaire, distributed to all 6121 emplo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(34 citation statements)
references
References 19 publications
2
32
0
Order By: Relevance
“…These findings were consistent with findings in other research where a higher level of academic training was predictive of higher research engagement (Finch et al, 2015). Practitioners in this study reported similar barriers and enablers to research as those in other health professions, including nursing, allied health and medicine (Akerjordet et al, 2012;Hiscock et al, 2014;Johnson et al, 2014;Marshall et al, 2016). While the most significant barriers were lack of time and research not being part of their work role (or not seen as being of value to their work role), barriers of 'not knowing what to research' and 'no interest in undertaking research' were identified by practitioners.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These findings were consistent with findings in other research where a higher level of academic training was predictive of higher research engagement (Finch et al, 2015). Practitioners in this study reported similar barriers and enablers to research as those in other health professions, including nursing, allied health and medicine (Akerjordet et al, 2012;Hiscock et al, 2014;Johnson et al, 2014;Marshall et al, 2016). While the most significant barriers were lack of time and research not being part of their work role (or not seen as being of value to their work role), barriers of 'not knowing what to research' and 'no interest in undertaking research' were identified by practitioners.…”
Section: Discussionsupporting
confidence: 91%
“…Furthermore, the definition of the health information profession could be broadened to specifically include research elements. Establishment of a centralised research support service or network would potentially build research capacity and facilitate more research (HIMAA, ,b, Marshall et al., ). This type of network would provide mentoring of participants through the design, ethics approval, analysis and publication phases; standardised and regulatory compliant processes; and an increase in professional leadership skills.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 A 2005 audit of the Australian and New Zealand (NZ) HSR community revealed that most health service researchers were part-time and held another professional role, such as teaching or administration; in addition, a minority of respondents had employment contracts of greater than 5 years (32%) and reported working with a critical mass of health service researchers (41%). 2 The authors of that audit, 2 along with other international examples 3,4 and an Australian survey of research activities in one health service, 5 suggested there is a need to build the capacity of the HSR community. However, there are no recent data on the characteristics of the HSR community in Australia and NZ.…”
Section: Health Services Research Communitymentioning
confidence: 99%
“…[10][11][12] However, publication in peerreviewed journals may not be a priority for service-based researchers, who may focus on other process-based metrics, such as clinical guideline development or implementation, cost-savings within a service or improved patient or professional knowledge or engagement. 5 An audit of Canadian-funded HSR reported close to one-third of HSR was conducted outside academic settings, such as regional health authorities (15%) and charitable organisations (16%). 4 These data suggest that much of HSR may be conducted outside academic settings and should be evaluated by metrics beyond publication and citation rates.…”
Section: Hsr Impacts and Barriersmentioning
confidence: 99%
See 1 more Smart Citation